The failures of a 'model' system: RSD in Canada - Evans Cameron, H (Refugee Studies Centre, University of Oxford, 2020)
The Canadian refugee system is often regarded as a model for refugee status determination. While there is much to learn from what it does well, there is just as much to learn from what it does badly.